2020
DOI: 10.1111/1365-2745.13394
|View full text |Cite
|
Sign up to set email alerts
|

Above‐ground plant metabolomic responses to plant–soil feedbacks and herbivory

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 54 publications
(66 reference statements)
2
39
1
Order By: Relevance
“…Furthermore, other recent work has shown that plant family and functional group can explain a large portion of the variation in fungal community structure 33,42,43 . Functional traits as well as growth and nutrient acquisition strategies [44][45][46] and chemical defenses 47,48 of the selected plant species likely have more similarities within than between groups. This may explain why the two groups have a driving effect on plant-soil feedbacks in plant communities, in greenhouses, and field studies 7,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other recent work has shown that plant family and functional group can explain a large portion of the variation in fungal community structure 33,42,43 . Functional traits as well as growth and nutrient acquisition strategies [44][45][46] and chemical defenses 47,48 of the selected plant species likely have more similarities within than between groups. This may explain why the two groups have a driving effect on plant-soil feedbacks in plant communities, in greenhouses, and field studies 7,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Ecometabolomic analyses in biodiversity and ecosystem functioning (BEF) studies manipulating diversity of grassland species showed that primary and secondary metabolomes of individual plant species change with plant diversity level (Huberty et al, 2020, Ristok et al, 2019, Scherling et al, 2010). These diversity-driven effects on plant metabolomes could be caused by plant-plant interactions or soil feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Soil feedbacks occur because plant species and plant communities facilitate specific soil microbial communities (Bardgett and van der Putten, 2014). Individual plants exposed to these different soil communities can respond by changing their metabolomic profiles (Huberty et al, 2020, Ristok et al, 2019). Similar effects were observed on trees using targeted metabolomic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of many native plant species is, at least partly, determined by interactions with the soil microbial community, native plant chemistry, soil nutrients, mutualists, and natural enemies (van der Putten et al ., 2001; Inderjit et al ., 2011b; Austin et al ., 2014; Kos et al ., 2015; Bonanomi et al ., 2017; Kostenko et al ., 2017; Heinen et al ., 2019; Veen et al ., 2019; Huberty et al ., 2020; Pineda et al ., 2020). For example, beneficial soil microbes can reduce negative effects of aboveground insect herbivory on plant growth (Pineda et al ., 2017, 2020; Heinen et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%